2022
DOI: 10.3389/fpsyg.2022.1025747
|View full text |Cite
|
Sign up to set email alerts
|

News consumption and green habits on the use of circular packaging in online shopping in Taiwan: An extension of the theory of planned behavior

Abstract: The COVID-19 pandemic is far from over as outbreaks continue to spread around the world. The demand for packaging bags and cartons has also risen sharply in e-commerce shopping and takeaways because consumers have changed their shopping habits during the pandemic. The primary purpose of this study was to explore the factors prompting consumers to accept and use circular packaging when they shop online. From January to February 2022, a total of 373 online questionnaires were completed. The results showed that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Furthermore, behavior control had a positive effect on intention, meaning that the more consumers were able to take action on purchasing frozen food through e-commerce under behavior control, the stronger the intention to buy frozen food through e-commerce. The results of this study are in accordance with the research of Lee & Ngoc (2010), finding that behavior control is a variable strongly influencing consumers' purchase intention in shopping online.…”
Section: Factors Influencing Consumer Intentions and Decisions To Pur...supporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, behavior control had a positive effect on intention, meaning that the more consumers were able to take action on purchasing frozen food through e-commerce under behavior control, the stronger the intention to buy frozen food through e-commerce. The results of this study are in accordance with the research of Lee & Ngoc (2010), finding that behavior control is a variable strongly influencing consumers' purchase intention in shopping online.…”
Section: Factors Influencing Consumer Intentions and Decisions To Pur...supporting
confidence: 90%
“…Many empirical studies have examined consumer purchasing decisions such as using the TPB approach developed by Ajzen (1991). Like other empirical studies using TPB (He et al 2019;Piroth et al 2020;Suleman 2018;Ilyas et al 2020;Ranadive 2015;Nosi et al 2019;Lee & Ngoc 2010;Listyowati et al 2020), subjective norm, behavioral control, and confirmed attitude factors influence consumers' intentions and decisions when shopping online.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging sustainable consumption and offering cost‐effective, accessible substitutes is necessary to educate consumers on the advantages of circular consumption (Coderoni & Perito, 2020; Garcia et al, 2021). Szilagyi et al (2022) and Lee (2022) have both suggested an association between pro‐sustainable information, circular habits, environmental concerns, and climate change. This connection highlights the significance of advocating for circular consumption to foster sustainable consumption patterns and resolve environmental concerns (Gutentag, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, information about the environmental benefits of circular habits, such as reuse and repair, can motivate consumers to adopt these practices (Lubowiecki‐Vikuk et al, 2021). A study by Lee (2022) found that news consumption positively affects environmental attitudes, subjective norms, perceived behavioral control and circular packaging. However, there are still gaps in the literature on the impact of environmental concerns and the search for pro‐sustainable information on circular consumption and habits (Abad‐Segura et al, 2020; Alcalde‐Calonge et al, 2022; Szilagyi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation